Análise de esforços e cálculo de fadiga no transporte de plataformas offshore - Roveri, Francisco Edward (1985)
The purpose of this work is to assess the structural effects and the cumulative fatigue damage that may occur in the transportation of jackets by barges and self elevating units, as well as to compare the actions of this installation phase with those of the "in place" phase. The structure is subjected to motions obtained in the analysis of similar system under environmental actions in irregular sea states. The ship motion analysis was carried out by using the strip method technique. The steady state of the structure is obtained by means of a linear deterministic dynamic analysis in the frequency domain. A deterministic approach is used in the prediction of the cumulative fatigue damage of the leg of the self elevating unit while a probabilistic one is used for the jacket.